The exploration of ARF1 screening assays to determine the drug status of ARF1 in cancer and malaria - Ntlantsana, Apelele (Rhodes University, Faculty of Science, Department of Biochemistry and Microbiology, 2020)
ARF GTPases are key regulators of the secretory and endocytic pathways. ARF1 is involved in the secretory pathway. ARF1 has been implicated in the endoplasmic reticulum to Golgi transport, function of the Golgi apparatus and transport from the trans-Golgi network to endosomes. ARFs cycle between active GTP-bound and inactive GDP-bound conformations. GDP/GTP cycling is regulated by large families of guanine nucleotide exchange factors (GEFs) and GTPase activating proteins (GAPs). ARF GEFs facilitate the activation of ARFs by mediating the exchange of GDP for GTP, while ARF GAPs terminate ARF function by stimulating the hydrolysis of the terminal phosphate group of GTP. Based on existing evidence gained from gene manipulation and cell biological investigations, ARF1 has been shown to be fundamentally important for cancer cell proliferation and metastasis and may be a promising target for the development of anti-cancer drugs. Additionally, the conservation of ARFs in eukaryotic organisms leads to an interesting question of whether a single drug target can be used to target multiple diseases. In this case, can a human cancer drug employed for cancer therapy be used in anti-malarial drug therapies? To confirm the drug target status of ARFs using chemical validation experiments, novel inhibitory compounds are needed. This requires the development of complex in vitro protein- protein interaction assays that can be used to screen chemical libraries for ARF GTPase inhibitors. In this study, we developed a fluorescence resonance energy transfer (FRET) assay and a novel in vitro colorimetric plate-based assay to detect the activation status of truncated human and Plasmodium falciparum ARF1. In the case of the FRET assay, active (GTP-bound) and inactive (GDP-bound) ARF1 could be distinguished with Z-factor values >0.5, suggesting that further development of the assay format to identify GEF and GAP inhibitors may be feasible. In the case of the colorimetric assay, robust signals could be detected and the assay was useful for detecting the activation status of ARF1. However, although the activation of ARF1 by the Sec7 domains of the BIG1 and ARNO was detectable, signals were not robust enough to employ in screening campaigns.
Keywords: ADP ribosylation; Golgi apparatus; Guanosine triphosphatase; G proteins; Malariotherapy; Malaria -- Research; Cancer -- Chemotherapy; Malaria -- Chemotherpay